Catalytic ozonation of phenol enhanced by mesoporous MnO2 prepared through nanocasting method with SBA-15 as template. Issue 4 (August 2020) - Zhang, Jianlin; Zhuang, Tao; Liu, Shanjun; Zhang, G.C.; Huo, Kaili
Highlights: Mesoporous MnO2 was prepared by nanocasting method with SBA-15 as template. The prepared MnO2 is of relatively high adsorption capacity. OH is identified as the main reactive oxygen species. Phenol was completely degraded, and TOC removal of 35 % was acquired in 30 min. Abstract: A mesoporous MnO2 (M-MnO2 ) was prepared by nanocasting method with SBA-15 as the hard template, and was investigated as an ozonation catalyst. The composition and morphology of the as-prepared MnO2 were characterized using X-ray diffraction analysis, transmission electron microscopy and surface area analysis. The ordered nanorods with high surface area (100 m 2 g −1 ) helped the mass transport and the active sites exposed, and thus enhanced the efficiency of catalytic ozonation. The adsorption capacity of M-MnO2 on phenol was about 8 times as high as that of the control MnO2 (C-MnO2 ) calculated by the Langmuir adsorption model(10.47 mgg −1 vs 1.20 mgg −1 ). Hydroxyl radical was identified as the main reactive oxygen species, and the hydroxyl radical yield from M-MnO2 is about 2-fold enhanced compared with that from C-MnO2 . Benefiting from the high mass transport and abundant active sites exposed, the TOC removal of phenol catalyzed by M-MnO2 (35%) was much better than that by C-MnO2 (27%)in 30 minutes.